Anti-aquaporin 4 antibody in Japanese multiple sclerosis: the presence of optic–spinal multiple sclerosis without long spinal cord lesions and anti-aquaporin 4 antibody. Issue 9 (16th August 2007) - Tanaka, Masami; Tanaka, Keiko; Komori, Mika; Saida, Takahiko
Abstract : Background: Anti-aquaporin 4 (AQP4) antibodies were found in patients with neuromyelitis optica (NMO) and Japanese optic–spinal multiple sclerosis (OSMS). Objective: To review the clinical features and investigate anti-AQP4 antibodies of Japanese patients with multiple sclerosis (MS), with or without long spinal cord lesions (LCL). Methods: Anti-AQP4 antibodies were examined in the sera of 128 consecutive Japanese patients by the immunofluorescence method using AQP4 transfected cells. Results: The 45 LCL-MS patients included 28 with a long spinal cord lesion extending contiguously over three vertebral segments on sagittal T2 weighted images (long T2 lesion) and 17 with segmental cord atrophy extending more than three vertebral segments. We identified 25 patients with anti-AQP4 antibody with LCL and anti-AQP4 antibody. Anti-AQP4 antibody was found in 12/17 (70.6%) LCL-MS patients with segmental cord atrophy, and in 13/28 (46.4%) LCL-MS patients without segmental long cord atrophy (p = 0.135, Fisher's exact test). Seropositive MS patients with LCL had more relapses than seronegative patients (p = 0.0004, Mann–Whitney U test). 9 patients with OSMS were negative for anti-AQP4 antibody who did not show LCL. Conclusion: These results suggest that an anti-AQP4 antibody is found not only in MS patients with long T2 lesions but also in patients with segmental cord atrophy extending more than three vertebral segments. It is a marker of LCL-MS showing frequent exacerbations. Japanese OSMS cases comprised those that were identical to NMO cases and those that were more closely related to classic MS.